Respecting the principle of best interests of the child in Canadian monitoring - Collins, Tara (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d’études canadiennes, 2010)
This paper considers the relationship between the procedural concern of monitoring international child rights and the general principle of best interests of the child. Canadian monitoring processes to determine the situation of child rights are analysed using the best interests principle as a lens. It is argued that despite the importance of the best interests principle in relation to monitoring, many Canadian actors or processes continue to reflect their priorities, preoccupations or authority—despite their limitations— because they know best or have authority to do so. This approach mirrors the traditional, outdated understanding of best interests of the child principle. In contrast, the best interests of the child principle in child rights sense demands recognition, reorientation and commitment to progress so that monitoring is guided and influenced by child rights. The paper concludes with a number of recommendations to advance the best interests principle in monitoring.